IAP-Mediated Protein Ubiquitination in Regulating Cell Signaling - Baptiste Dumétier; Aymeric Zadoroznyj; Laurence Dubrez (Cells, 2020)
Over the last decade, the E3-ubiquitine ligases from IAP (Inhibitor of Apoptosis) family have emerged as potent regulators of immune response. In immune cells, they control signaling pathways driving differentiation and inflammation in response to stimulation of tumor necrosis factor receptor (TNFR) family, pattern-recognition receptors (PRRs), and some cytokine receptors. They are able to control the activity, the cellular fate, or the stability of actors of signaling pathways, acting at different levels from components of receptor-associated multiprotein complexes to signaling effectors and transcription factors, as well as cytoskeleton regulators. Much less is known about ubiquitination substrates involved in non-immune signaling pathways. This review aimed to present IAP ubiquitination substrates and the role of IAP-mediated ubiquitination in regulating signaling pathways.